Horn of darkness : rhinos on the edge - Cunningham, Carol, 1954- (Oxford University Press, 1997)
The worlds rhinoceroses face extinction because a part of their anatomy is valued too much. Poachers hunt and slaughter them because their horns are treasured. Once an estimated 100,000 black rhinos roamed from the Sahara to the Cape of Good Hope but now less than 3 per cent remain. In all of Africa, there is but a single infenced population numbering more than 100 individuals, in the inhospitable barrens of the Namib Desert. The hunger for money has resulted in the deaths of more than 160 Zimbabwean poachers as they tried to kill fro the valuable horns, Few options remain to stop the deadly harvest, Although guarded sanctuaries may now be working in Kenya, elsewhere foot patrols, helicopters, and high tech solutions have been tried and most have failed. In 1989 a radical strategy has developed - cutting the horns, The rationale is simple. If a rhino has no horns, the incentive to kill it should disappear. What has since unfolded is a biological and political drama, Carol Cunningham and Joel Berger describe their passionate quest to help conserve Africa's black rhinos.; Arriving with their 19 month old daughter in the fiercely independent country of Namibia, they undertook a fascinating study to understand how horns are involved in the social lives of this charismatic species. This book blends natural history and biology, adventure and adrenaline. Africans and local attitudes. It moves beyond the typical nature study by bringing in real world components of conservation - the delicate mix of western science, politics and economics, and personal despair and hope.